Application of the Hamdi Method Using the Gold Value and Gold Index Methods on the Financial Aspects of Oil Palm Plantation Business in Kampar Indonesia - Agustin, Hamdi; Hamdi, Luthfia Ahluljannati; Hamdi, Lathifa Miftahul Jannati (Jurnal Cendekia Keuangan, 2025)
Introduction/Main Objectives: This study aims to test whether the assessment of the business feasibility study with the Hamdi method consisting of Gold Value Method (GVM) and Gold Index (GI) gives the same decision results as the assessment using the conventional method consisting of Net Present Value (NPV) and Profitability Index (PI). This research tries to test Mr. Zulkifli's oil palm plantation business plan in Kampar Riau. The results of this assessment will be useful as a consideration in making business development decisions. Background Problems: NPV is not used is the prohibition of interest, which is applied in both Islam and Christianity. Riba or riba refers to the charging of interest at any level, whereas modern beliefs impose interest at an unfair and disproportionate rate and develop in parallel with the periodic interest gain. Novelty: The Hamdi method presents a viable option for assessing the feasibility of a business from a financial perspective and contributes to the calculation methods that exist in this domain. Research Methods: This study uses descriptive and quantitative analysis of the feasibility of Mr. Zulkifli's oil palm plantation business, which is assessed based on conventional and sharia aspects. The feasibility analysis assessment is based on the conventional perspective, namely NPV, and PI. The feasibility assessment is based on Hamdi's Method, namely the GVM and the GI Method. Finding/Results: The findings show that the results of the feasibility decision using GVM are in line with the NPV calculation, and the results of the feasibility decision using GI are in line with the PI calculation. Conclusion: Hamdi's method is feasible for assessing the feasibility of a business from a financial aspect. Research limitation/implications: Hamdi's method is still not well-known and needs to be introduced to other researchers.